Prevalence of Cancer-related Fatigue among Women with Breast Cancer in Erbil City - Shinwy Bakhtyiar Radha; Yousif Muhammed Younis (Hawler Medical University, 2020)
Background and objective: Cancer-related fatigue is greatest frequent upsetting sense of tiredness or exhaustion can happen regardless of cancer type and could be experienced physically or emotionally, and or cognitively, that is associated with the tumor or its treatment. The current study aimed at assessing prevalence of cancer-related fatigue among women with breast cancer. Method: A descriptive cross-sectional study design was conducted from 8th of October 2018 to 8th October 2019. To find out the prevalence of cancer-related fatigue among female breast cancer patients at Nankali Hospital in Erbil city. A sample of 60 breast cancer patient was obtained through non-probability purposive convenience sampling techniques. Data were analyzed using Statistical Package for the Social Sciences version 23 for windows. Results: The results showed that the highest percentage of participants (45%) were from age group between 39-54, most of them were from urban area, graduated from primary school, married, however; 53.3% of breast cancer women they had family history of breast cancer. Regarding breast cancer stages, 40% of participants were in third stage. Most of the breast cancer patients were receiving chemotherapy treatment and they had surgery (81.7% and 71.7% respectively). Concerning cancer-related fatigue 75% of participants suffered from fatigue, nonetheless; fatigue severity among participants range from severe 53.3% to moderate 48.3%. Also, physical fatigue was a common type of fatigue among women with breast cancer. Conclusion: One of the most common complains symptom of patient with cancer is fatigue. Cancer-related fatigue impact physical, emotional, cognitive domains of patients'. Moreover, cancer-related fatigue has undesirable effect on patients, mood, daily task performance, and the patient's life.